Investigation of group A Streptococcus immune responses in an endemic setting, with a particular focus on J8. Issue 50 (29th November 2018) - Campbell, Patricia Therese; Frost, Hannah; Smeesters, Pierre R.; Kado, Joseph; Good, Michael F.; Batzloff, Michael; Geard, Nicholas; McVernon, Jodie; Steer, Andrew
Highlights: Studied antibodies to J8, a potential group A Streptococcus vaccine antigen. Presence of J8 antibodies following infection is fleeting, if existent at all. J8 antibodies would not be useful as a marker of population immunity. Evidence will be useful for planning clinical trials of the J8 vaccine. Abstract: Sustained control of group A Streptococcus (GAS) infections in settings of poverty has proven to be challenging, and an effective vaccine may be the most practical long-term strategy to reduce GAS-related disease burden. Candidate GAS vaccines based on the J8 peptide have demonstrated promising immunogenicity in mice, however, less is known about the role of J8 antibodies in the human immune response to GAS infection. We analysed the stimulation of J8 antibodies in response to infection, and the role of existing J8 antibodies in protection against subsequent infection, using data collected in the Fijian population: (1) cross sectional population serosurvey; (2) paired serum collection for assessment of M-specific and J8 antibody responses; and (3) longitudinal assessment of GAS infection and immunity. Median J8 antibody concentrations peaked in the 5–14 year age group, but there was no sustained increase with age. J8 antibody concentration was neither a significant predictor of time to next infection, nor did it show any relationship to the time since last recorded skin infection. Similarly, J8 antibody fold changes over a defined period were associated neither with the time since last skin infection, nor the number of intervening skin infections. While strong M-specific antibody responses were observed for skin infection, similarly strong J8 antibody responses were not observed. There is no indication that antibodies to the J8 antigen would be useful as either a marker of GAS infection or a measure of population immunity, with J8 antibody responses to infection fleeting, if existent at all.